Manajemen Sumber Daya Manusia Untuk Meningkatkan Mutu Pendidikan Di SMP IT An-Nuriyah Sekayu - Rafli Sandika Pratama; Amilda; Asep Rohman (CV. ITTC INDONESIA, 2023)
This thesis is entitled â€œManagement of Human Resources to Improve the Quality of Education at SMP It An-Nuriyah Sekayuâ€. This research aims to determine the management of human resources to improve the quality of education at SMP IT An-Nuriyah Sekayu and to know how to plan, organize, implementation and supervision of human resources at SMPIT An-Nuriyah Sekayu. In this study, researchers used a qualitative descriptive approach using qualitative research. In this study, the research informants were the principal, deputy head of curriculum, and the data collection teacher used were observation, interviews, and documentation. The techniques used in data analysis were data reduction, data presentation, data verification and conclusion. Data validity test This study uses data source triangulation and method triangulation. The results of this study indicate that human resource management to improve the quality of education at SMPI AN-Nuriyah Sekayu is carried out. implementation and supervision. Human resource planning that is designed regarding the recruitment process, Organizing human resources by setting tasks, to provide task directions to teaching and educational staff their work assignments in accordance with their respective decrees, Implementation of school principals' HR provides direct work motivation during working hours and outside working hours so that educators and education staff can work well, and direct HR supervision. In this study, the authors concluded that human resource management for improving the quality of education at SMPIT An-Nuriyah Sekayu was quite good. With the planning, organizing, implementing, and supervising of human resources by the principal and waka of the curriculum, human resource management to improve the quality of education runs effectively and efficiently.